The relationship between throwing velocity and motor ability parameters of the high-performance handball players - Eliasz, J. (ISBS - Conference Proceedings Archive (Konstanz), 1995)
The aim of the research was to find the relationships between the ball velocity during different types of throws in handball and basic motor ability parameters (muscle strength, arm speed) of players, in order to improve the efficiency of training. MATERIAL AND METHODS. Twelve high-performance handball players took part in the experiment (six of them were at that moment members of the National Team). The average values of basic parameters of physical characteristics of the subjects were: 89.0±7.8 kg (body mass), 1.88±0.05 m (body height) and 23.3±2.5 years of age. The Shapiro-Wilk test, Pearson's correlation matrix and multiple regression analysis were used (a=0.05). Conclusions 1.Statistically significant differences were found between maximal ball velocity during throws with a cross-over step, and ball velocities during other analyzed throws. The highest ball velocity was achieved during the throw with a cross-over step performed by play-makers. 2. Among the motor ability factors, total muscle strength of the body (ISI), strength of trunk flexors (abdominal muscles) and maximal arm (shoulder joint) angular velocity (MSD) have a decisive effect on the ball velocity in analyzed throwing techniques. 3. The maximal arm speed is the most important factor determining ball velocity during - technically the simplest - throw on the spot. Muscle strength has greater influence on ball velocity during - technically more complicated - throw with an upward jump.